Safety and efficacy of OptiPhos(®) PLUS for poultry species for fattening, minor poultry species reared for breeding and ornamental birds - Bampidis, Vasileios (EFSA J, 2020)
Following a request from the European Commission, the Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) was asked to deliver a scientific opinion on OptiPhos PLUS (®) to be used as a feed additive for chickens for fattening, chickens reared for laying, turkeys for fattening, turkeys reared for breeding, minor poultry species for fattening, minor poultry species reared for laying, minor poultry species reared for breeding and ornamental birds. The active substance is 6‐phytase produced by a genetically modified strain of Komagataella phaffii. The FEEDAP Panel concludes that the genetic modification of the production strain does not give rise to safety concerns. Based on the tolerance studies provided, the Panel concludes that the additive is safe for the target species under the conditions of use with a wide margin of safety. The additive is not a skin irritant. It is found to be a dermal sensitiser. The FEEDAP Panel cannot conclude on the eye irritation potential of the additive. Owing to the proteinaceous nature of the active substance, the additive is considered a respiratory sensitiser. The FEEDAP Panel concludes that the additive has the potential to be efficacious in increasing the phosphorus utilisation in chickens for fattening at the level of 250 FTU/kg feed. These conclusions can be extended to turkeys for fattening and chickens and turkeys reared for laying/breeding and extrapolated to all minor poultry species and other avian species up to the point of lay.